Exploring Students' Perceptions and Experiences of Learning Vocabulary through Short Stories in An EFL Classroom - Siskayanti, Siskayanti; Indah, Chindy Hanggara Rosa; Sari, Ike Dian Puspita (UIBU, 2026)
This study examined first-year English Language Education students’ perspectives on utilizing short stories for vocabulary enrichment at a private university in Malang, Indonesia. Employing a descriptive qualitative design, the study involved 10 purposively selected participants characterized by limited initial vocabulary proficiency. Over a four-week period, the students read four flash fiction stories integrated with structured pre-reading, while-reading, and post-reading vocabulary activities. Data were collected through semi-structured interviews and analyzed thematically. The findings revealed four primary themes: predominantly positive perceptions, significant benefits for vocabulary acquisition, manageable linguistic and pedagogical challenges, and practical suggestions for instructional improvement. Participants viewed short stories as significantly more engaging and effective than traditional decontextualized word-list methods, noting that contextualized narrative exposure enhanced contextual retention and syntactic understanding. Although some participants encountered difficulties regarding complex vocabulary and time constraints, they considered these challenges surmountable. The study concludes that short stories offer a highly viable alternative for vocabulary development in English as a Foreign Language (EFL) settings, providing pedagogical recommendations for lecturers and directions for future research.